SARS-CoV-2 breakthrough infections elicit potent, broad, and durable neutralizing antibody responses - Walls, Alexandra C.; Sprouse, Kaitlin R.; Bowen, John E.; Joshi, Anshu; Franko, Nicholas; Navarro, Mary Jane; Stewart, Cameron; Cameroni, Elisabetta; McCallum, Matthew; Goecker, Erin A.; Degli-Angeli, Emily J.; Logue, Jenni; et al. (Cell, 2022)
Although infections among vaccinated individuals lead to milder COVID-19 symptoms relative to those in unvaccinated subjects, the specificity and durability of antibody responses elicited by breakthrough cases remain unknown. Here, we demonstrate that breakthrough infections induce serum-binding and -neutralizing antibody responses that are markedly more potent, durable, and resilient to spike mutations observed in variants than those in subjects who received only 2 doses of vaccine. However, we show that breakthrough cases, subjects who were vaccinated after infection, and individuals vaccinated three times have serum-neutralizing activity of comparable magnitude and breadth, indicating that an increased number of exposures to SARS-CoV-2 antigen(s) enhance the quality of antibody responses. Neutralization of SARS-CoV was moderate, however, underscoring the importance of developing vaccines eliciting broad sarbecovirus immunity for pandemic preparedness. [Display omitted] •Breakthrough infections induce potent neutralizing antibody responses•Number of exposures (infection or vaccination) correlates with potency and breadth•Three-dose vaccination improves neutralization of the SARS-CoV-2 Omicron variant•SARS-CoV-2 infection or vaccination elicit moderate neutralization of SARS-CoV Individuals with breakthrough COVID-19 infections, previously infected/vaccinated individuals, and those vaccinated thrice have potent serum-binding and -neutralizing antibody responses against variants of concern, including Omicron. Neutralization of SARS-CoV, however, was moderate, thus urging the need for developing broad vaccines for pandemic preparedness.